El software educativo JCLIC, como herramienta didáctica para el aprendizaje del bloque geométrico y medida, de los estudiantes del décimo grado de educación general básica de la unidad educativa anexa a la Universidad Nacional de Loja, de la ciudad de Loja, periodo 2013 -2014 - Duarte Cango, Andrea Ximena (2015)
The research aimed to use JClic EDUCATIONAL SOFTWARE AS EDUCATIONAL TOOL FOR LEARNING THE GEOMETRIC BLOCK AND EXTENT OF TENTH GRADE STUDENTS BASIC GENERAL EDUCATION Education Unit attached to the National University of Loja. The overall objective of the research process is applied JCLIC educational software as a teaching tool to optimize learning Geometric Block and Measurement The research responded to a descriptive design (diagnosis) and experimental pre. The phases that were used in their order were: understanding in which a detailed knowledge of the contents of Geometric Block and Measurement on the basis was established for a compilation to know the context of the object of research, diagnosis in which it was applied a survey with questions of content to students, teachers and parents getting information to identify factors that hinder learning model in which an action or instrument is determined as an alternative to enhance learning; JCLIC with which different media activities, implementation phase in which workshops were conducted using the JCLIC educational software as a teaching tool for learning Geometric Block and Measurement and assessment of the effectiveness of this alternative JCLIC based educational software developed to rank Wilcoxon sign test statistic. The main finding: difficulty in defining and measuring angles, gaps in identification of trigonometric functions of an acute angle, to optimize cognitive learning geometric measurement block and needs; you can reduce or mitigate the application of educational software JCLIC as a teaching tool for learning geometry and measurement block. Application of educational software as a teaching tool JCLIC learning and Measurement Geometric Block the following significant results were obtained: The variability between pretest and post test when applying JCLIC educational software as a teaching tool for learning Geometric Block and Measurement calculated through the sign test - Wilcoxon rank is 0.0001. The value obtained through the sign test - Wilcoxon rank indicates JCLIC educational software as a teaching tool for learning and Measurement Geometric Block is an effective alternative in enhancing learning the trigonometric functions of an acute angle, and for measuring angles.